Post-operative wound complications following emergency and elective abdominal surgeries - Dhaigude, B. D.; Shree, Shilpi; Shah, Priti; Francis, Merry; Patel, Keyur; Metta, Vipul (International Surgery Journal, 2017)
Background: The post-operative wound complications can be defined as any negative outcome as perceived either by the surgeon or by the patient. Objectives were to study the early and late post-operative wound complication of patients undergoing emergency and elective abdominal surgery, to find out and compare the incidence of post-operative wound complications following emergency and elective abdominal surgery and to find out and compare the factors associated with wound complications following elective and emergency abdominal surgery. Methods: The study was conducted at Dr. D. Y. Patil Medical College and Hospital, DPU University, for a period of 2 years (from July 2015-September 2017) and is a prospective type of study using 100 cases (Group A: Elective and Group B: Emergency abdominal surgeries –50 each). The study was approved by the Institute’s Ethics Committee. Results: 100 patients were operated in our study. The type of collection from surgical site was seropurulent in 4 (8%) patients and purulent in 1 (2%) patient of Group A whereas it was seropurulent in 5 (10%) patients and purulent in 1 (2%) patient of Group B. The type of collection in Closed Suction Drain was Serous in 12 (24%) patients, Serosanguineous in 10 (20%) patients and Seropurulent in 1 (2%) patient of Group A whereas it was Serous in 13 (26%) patients, Serosanguineous in 10 (20%) patients and Seropurulent in 1 (2%) patient of Group B. The post-operative hospital stay for majority of the patients in Group A was ≤10 days (82%) while it was 11-14 days for Group B (54%). Conclusions: Possible complications following elective surgery and those following urgent/emergency surgery, a debatable issue was the possibility of significant differences between them. The emergency laparotomies are also more common than elective laparotomies especially at peripheral centers. These findings suggest that wound complications do occur in elective abdominal surgeries. These can be reduced to a certain extent by careful case selection, improving Hb levels prior to surgery, using adequate prophylaxis and better surgical practices.